Epithelioid hemangioendothelioma of right innominate vein mimics a teratoma: A case report. Issue 9 (March 2017) - Wan, Qi; Zhou, Jiaxuan; Yu, Yudong; Sun, Qingyu; Bao, Yingying; Lei, Qiang; Zou, Qiao; Deng, Yingshi; Li, Xinchun
Abstract: Rational: Epithelioid hemangioendothelioma (EHE) is a rare neoplasm commonly known to arise from the soft tissue, lung, and liver. EHE arising from right innominate vein (RIV) has scarcely been reported in English literature. Patient concerns: Herein, we present a rare case of EHE of RIV in a 51-year-old woman with right-lower chest pain for 4 days. Computed tomography of the chest revealed a spherical mass with calcification and fatty foci located in the anterior mediastinum, thus a presumptive diagnosis of teratoma was made. Diagnoses, interventions, and outcomes: Video-assisted thoracoscopic explorations and resection of mediastinal tumor were then performed. The pathological examination showed that the tumor was EHE. Postoperative radiotherapy was delivered to the patient. Pulmonary metastases were found by chest CT a year after surgery. Lessons: A diagnosis of EHE might be considered, when a mediastinal tumor closely related to veins showing intratumoral calcification and obvious enhancement, despite the presence of a clear boundary and visible fat content.